Workplace Bullying and Post-Traumatic Stress Disorder Symptoms: a Double Mediation Model - Minibas-Poussard, Jale; Idig-Camuroglu, Meltem; Seckin-Celik, Tutku; Bingol, Haluk Baran (International Journal of Contemporary Economics and Administrative Sciences, 2022)
The purpose of this study is to explore the interlinkage of emotion-focused coping and perceived stress in the relationship between workplace bullying and post-traumatic stress disorder(PTSD) symptoms. This study was a cross-sectional, nation-wide survey, with sampling in ten cities across Turkey.The sample (N=257) is composed of employees who reported high exposure to bullying. The scales used are workplace bullying, PTSD symptoms, perceived stress and emotion-focused coping. Through a double mediation model, results demonstrate that the relationship between workplace bullying and PTSD symptoms is affected by the interaction between emotion-focused coping and perceived stress. This study contributes to fill the gap in the workplace bullying literature by focusing on person-related factors. To our knowledge, the mediator role of perceived stress and emotion-focused coping has not been studied together yet in the workplace bullying and PTSD research. Workplace bullying has important organizational and economic consequences as well as individual serious health problems. HRM implications are discussed to prevent victims to get into a vicious cycle.